2020
DOI: 10.1111/ctr.13903
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to immediate release tacrolimus in solid organ transplant recipients: When the gold standard is in short supply

Abstract: Tacrolimus is an immunosuppressant that exerts its activity via suppression of cellular immunity by binding to FKBP-12 to form a complex with calcineurin-dependent proteins to inhibit calcineurin phosphatase activity and subsequently T lymphocyte activation. Approved by the Federal Drug Administration (FDA) under the brand name Prograf ® in 1994, immediate-release tacrolimus (IR-TAC) is now considered the backbone of maintenance immunosuppressive regimens in solid organ transplantation (SOT). In the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Indeed, tacrolimus alternatives are plagued with reduced efficacy in the prevention of allograft rejection, which must be weighed in the risk–benefit assessment, given the association of rejection versus long-term cardiovascular risk. 120 A careful evaluation of the patient’s overall risk of rejection should be done before switching to belatacept, and patients should be followed closely after conversion.…”
Section: Risk Factors Of Cvd In Ktrsmentioning
confidence: 99%
“…Indeed, tacrolimus alternatives are plagued with reduced efficacy in the prevention of allograft rejection, which must be weighed in the risk–benefit assessment, given the association of rejection versus long-term cardiovascular risk. 120 A careful evaluation of the patient’s overall risk of rejection should be done before switching to belatacept, and patients should be followed closely after conversion.…”
Section: Risk Factors Of Cvd In Ktrsmentioning
confidence: 99%
“…According to reports, the occurrence of CNI-related renal damage after lung transplantation is closely related to the dosage of CNI. Reducing the dosage of CNI and controlling the blood concentration within a certain range play an important role in reducing the occurrence of nephrotoxicity [ 23 ]. Previous studies have found that CNI has obvious and clear nephrotoxicity in kidney transplantation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insurance companies may deny these medications that are necessary for graft and patient survival. Furthermore, the transplant community continues to struggle with the ongoing shortage of immediate‐release tacrolimus, which has required us to utilize off‐label medications such as LCPT in non‐FDA approved organ indications to prevent disruptions in therapy 34 . This report not only provides critical reference data that may be actionable to expand immunosuppression options and access to heart transplant recipients, but also highlights the need to continue to work on prioritization of heart transplant specific trials to ensure optimal use of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%